Disorder-specific alterations of tactile sensitivity in neurodevelopmental disorders - Jason L. He (Nature Portfolio, 2021)
He et al. assessed different parameters of tactile processing in children diagnosed with autism spectrum disorders (ASD) and attention-deficit/hyperactivity disorder (ADHD). They found evidence for disorder-specific alterations of lower-level sensory processing, which can be related back to higher-level clinical symptoms.